2019
DOI: 10.1007/s40199-019-00240-z
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 for overcoming drug resistance in solid tumors

Abstract: Objectives In this review, we focus on the application of clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR associated nuclease 9 (Cas9), as a powerful genome editing system, in the identification of resistance mechanisms and in overcoming drug resistance in the most frequent solid tumors. Data acquisition Data were collected by conducting systematic searching of scientific English literature using specific keywords such as Bcancer^, BCRISPR^and related combinations. Results The review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Accumulating evidence revealed that the CRISPR-Cas9 geneediting tool can be considered as a potential approach in order to promote sensitivity to chemotherapeutic agents. Due to the reason that gene mutation plays a remarkable role in developing drug resistance in tumor cells, CRISPR-Cas9 can be employed as an effective gene manipulation system with regards to permanently removing genes and attenuating resistance to cancer chemotherapy (149)(150)(151). Furthermore, this applicable method can be applied effectively and has a great advantage compared to other gene-editing technologies such as siRNAs, ZFNs, and TALENs in manipulating target genes involved in the chemotherapy resistance (152)(153)(154).…”
Section: Application Of the Crispr/cas9 System With The Aim Of Overcoming 5-fu Resistance In Human Cancer Cellsmentioning
confidence: 99%
“…Accumulating evidence revealed that the CRISPR-Cas9 geneediting tool can be considered as a potential approach in order to promote sensitivity to chemotherapeutic agents. Due to the reason that gene mutation plays a remarkable role in developing drug resistance in tumor cells, CRISPR-Cas9 can be employed as an effective gene manipulation system with regards to permanently removing genes and attenuating resistance to cancer chemotherapy (149)(150)(151). Furthermore, this applicable method can be applied effectively and has a great advantage compared to other gene-editing technologies such as siRNAs, ZFNs, and TALENs in manipulating target genes involved in the chemotherapy resistance (152)(153)(154).…”
Section: Application Of the Crispr/cas9 System With The Aim Of Overcoming 5-fu Resistance In Human Cancer Cellsmentioning
confidence: 99%
“…71 CRISPR-Cas9-mediated depletion of a centriole satellite protein PCM1 revealed that its removal inhibited glioblastoma cell proliferation and had increased sensitivity to temozolomide in patient-derived glioblastoma. 72 Saber et al 73 and Liu et al 74 have reviewed these studies.…”
Section: Crispr-cas9 As a Tool To Overcome Drug Resistance In Cancermentioning
confidence: 99%
“…It indicates CRISPR-mediated disruption of EGFR may be a promising therapeutic option for RCC in the future [21]. Given the importance of EGFR overexpression for tumor survival, growth and drug resistance, future studies are needed to explore whether overexpressed EGFR knockout can be an option for more cancers [22]. However, for clinical use, optimization of the delivery methods for specifically targeting overexpressed EGFR in cancer cells needs more in depth investigations [23]; for instance, optimization of specific gene therapy delivery vehicles based on EGFR [24] We showed a higher level of MAPK/pERK in RC21 EGFR -/cells as compared to the EGFR wt/wt cells indicative of a bypass mechanism for activation of MAPK/pERK pathway upon loss of EGFR.…”
Section: Plos Onementioning
confidence: 99%